Existence theory for quasilinear elliptic equations via a regularization approach - Liu, Jiaquan; Liu, Xiang-Qing; Wang, Zhi-Qiang (Topological Methods in Nonlinear Analysis, 2017)
In this paper, we further develop a regularization approach initiated in our earlier work for the study of solution structure of quasilinear elliptic equations containing several special cases of mathematical models.